Ekokritik dalam Sastra Indonesia: Kajian Sastra yang Memihak - Dewi, Novita (Sunan Kalijaga State Islamic University Yogyakarta, 2016)
Literary studies of high quality require at least two things: (1) an increase on the weight and depth of appreciation of the literary works under investigation, and (2) the study’s social contribution towards the factual problems in society. The study of literature should involve the production of useful knowledge, instead of formal academic compliance. This paper is to discuss one possible type of study on Indonesian literature, i.e. ecocritical reading of literature. When examined closely through today’s politically contextual lenses and the implications thereof, Indonesian literature on environment and literary filmization can result in useful and referential knowledge. Studies of this kind differ significantly in terms of quality from a mere textual analysis of literary works with a brief, shallow description of some literary terminologies that function only as scientific embellishments. The objective of this article, therefore, is to discuss studies on Indonesian Literature using Ecocriticism as one possible trajectory to transform society.